Intrinsic Class D β-Lactamases of Clostridium difficile - Marta Toth (American Society for Microbiology, 2018)
ABSTRACT Clostridium difficile is the causative agent of the deadly C. difficile infection. Resistance of the pathogen to β-lactam antibiotics plays a major role in the development of the disease, but the mechanism of resistance is currently unknown. We discovered that C. difficile encodes class D β-lactamases, i.e., CDDs, which are intrinsic to this species. We studied two CDD enzymes, CDD-1 and CDD-2, and showed that they display broad-spectrum, high catalytic efficiency against various β-lactam antibiotics, including penicillins and expanded-spectrum cephalosporins. We demonstrated that the cdd genes are poorly expressed under the control of their own promoters and contribute only partially to the observed resistance to β-lactams. However, when the cdd1 gene was expressed under the control of efficient promoters in the antibiotic-sensitive Clostridium cochlearium strain, it produced high-level resistance to β-lactams. Taken together, the results determined in this work demonstrate the existence in C. difficile of intrinsic class D β-lactamases which constitute a reservoir of highly potent enzymes capable of conferring broad-spectrum, clinically relevant levels of resistance to β-lactam antibiotics. This discovery is a significant contribution to elucidation of the mechanism(s) of resistance of the clinically important pathogen C. difficile to β-lactam antibiotics. IMPORTANCE C. difficile is a spore-forming anaerobic bacterium which causes infection of the large intestine with high mortality rates. The C. difficile infection is difficult to prevent and treat, as the pathogen is resistant to many antimicrobial agents. Prolonged use of β-lactam antibiotics for treatment of various infectious diseases triggers the infection, as these drugs suppress the abundance of protective gut bacteria, allowing the resistant C. difficile bacteria to multiply. While resistance of C. difficile to β-lactam antibiotics plays the major role in the development of the disease, the mechanism of resistance is unknown. The significance of our research is in the discovery in C. difficile of β-lactamases, enzymes that destroy β-lactam antibiotics. These findings ultimately can help to combat deadly C. difficile infections.